2000
DOI: 10.1097/00005344-200003000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olprinone, Phosphodiesterase III Inhibitor, on Cerebral Blood Flow Assessed with Technetium-99m-ECD SPECT

Abstract: Few clinical reports exist regarding the effects of phosphodiesterase III inhibitors on cerebral arteries. Therefore we used a [99mTc]-ECD brain SPECT and an ultrasound method to quantitatively evaluate cerebral and systemic flow dynamics after the administration of olprinone, a phosphodiesterase III inhibitor. In 15 patients (65 +/- 8 years, M/F = 13/2) with no abnormalities on a brain computed tomography (CT), cerebral blood flow and cardiac output were measured using [99mTc]-ECD brain SPECT and Doppler echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Although olprinone increased cardiac output due to the positive inotropic action (2 to 48% increase in cardiac output), systemic vascular resistance decreased due to the vasorelaxant effect of the drug. There was no significant correlation between percentage change in CBF and cardiac output (50) (Fig. 3).…”
Section: Effects On Cerebral Circulation Normal Subjectsmentioning
confidence: 89%
See 2 more Smart Citations
“…Although olprinone increased cardiac output due to the positive inotropic action (2 to 48% increase in cardiac output), systemic vascular resistance decreased due to the vasorelaxant effect of the drug. There was no significant correlation between percentage change in CBF and cardiac output (50) (Fig. 3).…”
Section: Effects On Cerebral Circulation Normal Subjectsmentioning
confidence: 89%
“…Previous studies have shown that rCBF is significantly reduced in patients with cerebral infarct areas, as compared to patients without lesions, because cerebrovascular resistance due to advanced arteriosclerosis or excessive vasoconstriction may have been increased in patients with cerebral infarction (27). The effect of olprinone on rCBF has little relation to hemodynamic changes, including cardiac output or systemic blood pressure (6,50). We considered that the effect of olprinone on rCBF is likely to be due to a direct action of the drug on the smooth muscle of small cerebral vessels (7,26,39).…”
Section: Patients With Arteriosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the augmentation effect of olprinone on CBF showed no significant correlation with cardiac output measured by Doppler echocardiography in normal elderly subjects [7]. This may suggest that the acute increase in cardiac output due to the improvement in cardiac function is not important for an increase in CBF [2, 7]. In addition, we concluded that excessively fast responses of hormonal systems and cerebral vessels to the hemodynamic changes 15 min after the initiation of olprinone infusion were unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Olprinone, a phosphodiesterase-3 inhibitor, has been used to treat acute heart failure due to its positive inotropic and vasodilation effects, and it also augments CBF of the normal cerebral cortex [6, 7]. However, little data exist on the effects of olprinone on CBF in heart failure patients.…”
Section: Introductionmentioning
confidence: 99%